Internationalization of Islamic Character Values Among Students at Husnul Khotimah Foundation, Kuningan Regency - Insan Nulyaman; Uus Ruswandi; Aan Hasanah; Asep Nursobah (International Journal of Social Service and Research, 2022)
The purpose of this study was to determine the values, processes, supporting and inhibiting factors as well as an evaluation of the internalization of character values in students in the perspective of Islamic education in Madrasah Tsanawiyah and Madrasah Aliyah, educational institutions are not just transferring knowledge to students, but more than that the institution must be able to internalize character values to students, because education is the right place or place in building a nation of character. The method used in this research is descriptive analytical research method. The results of the study are (1) types of character values in students in the perspective of Islamic Education at MTs and MA Husnul Khotimah Kuningan Regency are straight faith, strong character, strong body, broad insight, and good at keeping time, (2) the purpose of internalizing character values in students in the perspective of Islamic Education in MTs and MA to become reliable and professional da'i cadres, (3) the process of internalizing character values in students in the perspective of Islamic Education through classical teaching and learning processes in the classroom and through the process of education and training in extracurricular activities, (4) supporting factors include student talents and interests, madrasa policies, human resources including madrasa stakeholders, facilities and infrastructure, curriculum, methods and roles of parents and alumni. While the inhibiting factor for internalizing character values in classical teaching and learning activities in the classroom and extracurricular activities is the number of activity schedules, and (5) evaluation of the internalization of character values in students in the perspective of Islamic Education in MTs and MA internalization of values using observation techniques, interviews and documentation studies